Common peroneal nerve palsy: a clinical and electrophysiological review. - Berry, H (1976)
In a series of 70 patients (75 cases of common peroneal nerve palsy) the common causes were trauma about the knee or about the hip, compression, and underlying neuropathy. A few palsies occurred spontaneously for no apparent reason. The prognosis was uniformly good in the compression group; recovery was delayed but usually satisfactory in patients who had suffered stretch injuries. In the acute stage, when clinical paralysis appears to be complete, electrophysiological studies are a useful guide to prognosis. They may also indicate an underlying neuropathy and they detect early evidence of recovery. The anatomical peculiarities of the common peroneal nerve are noted and aspects of the clinical picture, management, and prognosis of palsy are discussed.